The Impact of Social Media on the Sustainability of Fashion Industry Marketing - Ivana Bolanča Mirković; Katarina Itrić Ivanda; Zdenka Bolanča; Marina Vukoje (Tehnički Glasnik)
In the second decade of the 21st century, there were significant changes in the strategies for implementing marketing campaigns. The fashion industry quickly accepted and improved the ways of conducting marketing campaigns. The market requires quick-changing trends, which is evident both in the rapid production of clothing items and in new marketing campaigns. Customers eager for interactivity and viewing trends at a time that suits them, often view fashion novelties on social media. The desire for the representation of fashion brands on as many social network applications as possible greatly contributes to increasing the impact of reducing the quality of the environment. Users need large amounts of energy to browse new trends. Posts of trendy fashion items are often shared in groups or circles of friends, increasing the energy needed. Systems for storing media content require a large amount of energy needed to store data from social media and to cool the system. All the above contributes to the emission of greenhouse gases and the reduction of non-renewable energy sources because unfortunately, renewable energy sources are not yet sufficient for all the listed needs. In research, the habits of respondents related to the use of social media related to fashion items are studied. In addition to the aforementioned, knowledge related to the awareness and knowledge of respondents regarding the influence of social media on the sustainability of marketing drips of the fashion industry was collected. The mentioned topic is not close to the respondents, although most of the respondents were undergraduate graphic design students who may participate in marketing campaigns in the future.